150k views
2 votes
Simplify.
(picture provided, thank you so much)​

Simplify. (picture provided, thank you so much)​-example-1
User Smk
by
4.9k points

2 Answers

4 votes

Answer:

Explanation:


-5x^(4)*(-3x^(2) + 4x - 2) = (-5x^(4) * -3x^(2))+(-5x^(4)*4x)-(-5x^(4)*2)\\\\=15x^(4+2)+(-20x^(4+1))-(-10x^(4))\\\\=15x^(6)-20x^(5)+10x^(4)

User Gurbela
by
5.2k points
4 votes

-5x^4(-3x^2 + 4x -2)

Multiply the number on the outside by each number inside the parentheses:

-5x^4 x -3x^2 = 15x^6

-5x^4 x 4x = -20x^5

-5x^4 x -2 = 10x^4

Now combine them in order of exponents:

15x^6 - 20x^5 + 10x^4

User Evan Broder
by
6.0k points